The Analysis of the Effectiveness of Online Learning Media for the Students During the Covid-19 Pandemic - Priyastuti, Maria Theresia; Suhadi, Suhadi; Selano, Maria Karolina (Journal of Language and Health, 2021)
This study discusses the analysis of the effectiveness of online learning media for the students during the covid-19 pandemic. This research is to know the effectiveness of online media for the students during the covid 19 pandemic. The method used is quantitative descriptive research with a total sampling of students of Stikes St. Elisabeth Semarang during the online learning process by giving questionnaires related to online learning media during the covid-19 period. The results obtained that most of the students at Stikes St. Elisabeth often uses Google Meet (GM) learning media and likes online learning through Google Meet (GM). The most frequently used feature of GM is the presentation form. The conclusion is that GM is an effective and efficient learning media during the covid-19 pandemic.